2019
DOI: 10.1002/ppul.24227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sweat test systems for the diagnosis of cystic fibrosis in newborns

Abstract: Objectives In the national newborn screening programme for CF in Switzerland, we compared the performance of two sweat test methods, by investigating the feasibility and diagnostic performance of the Macroduct® collection method (with chloride mesurement) and Nanoduct® test (measuring conductivity) for diagnosing CF. Study‐Design We included all newborns with a positive screening result between 2011 and 2015 who were referred to a CF‐centre for sweat testing. In the CF‐centre, a Macroduct and Nanoduct sweat te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A sufficient amount of sweat is needed to determine the chloride concentration; the smaller the children are or the lighter they are, the more difficult it is to obtain sufficient sweat. A sweat test should not be performed in children <2 kg, and the rates of sweat collections with insufficient volume (called Quantity Not Sufficient, QNS) are below 10% if the child weighs ≥4 kg [15,16]. Collecting sweat from two sites (left and right arm), as is recommended in the US, can reduce the QNS rate.…”
Section: Sweat Test-the Gold Standard Confirmation Test Of a Positivementioning
confidence: 99%
See 1 more Smart Citation
“…A sufficient amount of sweat is needed to determine the chloride concentration; the smaller the children are or the lighter they are, the more difficult it is to obtain sufficient sweat. A sweat test should not be performed in children <2 kg, and the rates of sweat collections with insufficient volume (called Quantity Not Sufficient, QNS) are below 10% if the child weighs ≥4 kg [15,16]. Collecting sweat from two sites (left and right arm), as is recommended in the US, can reduce the QNS rate.…”
Section: Sweat Test-the Gold Standard Confirmation Test Of a Positivementioning
confidence: 99%
“…Nanoduct™ is a newer sweat conductivity analysis system that was specially developed for newborns as it requires only 3–5 μL of sweat and measures conductivity in situ [ 28 ]. A few studies have assessed and confirmed its ability to discriminate between those affected by CF and healthy children [ 16 , 29 , 30 , 31 , 32 , 33 ]. According to current guidelines, conductivity measurement is an accepted method to rule out CF, but for a definite diagnosis, the determination of sweat chloride is required as it is better validated [ 9 , 14 , 24 ].…”
Section: Sweat Test—the Gold Standard Confirmation Test Of a Positmentioning
confidence: 99%
“…It was developed especially for use with newborns, and only 3 μL of sweat is required. As soon as sweat enters the microconductivity cell, the ST result is shown on the display ( 35 ).…”
Section: Other St Methodsmentioning
confidence: 99%
“…In 1959, Gibson and Cooke published a method for sweat induction by pilocarpine iontophoresis on a small body surface area [ 6 ], and it remains the diagnostic gold standard for CF even today. Measuring conductivity by Nanoduct ® can facilitate the diagnosis of screening-positive newborns, but is less specific than the sweat chloride measurement [ 7 ] and not recommended as a diagnostic measurement [ 8 ].…”
Section: Changing Face Of Cystic Fibrosismentioning
confidence: 99%